Analysis of Nanoporous Semiconductor Film Thickness Effect on Short Circuit Current Density of β-Carotene Dye based DSSC: Theoretical and Experimental Approach - Solehudin Solehudin; Markus Diantoro; Arif Hidayat (Universitas Negeri Malang, 2019)
Dye-sensitized solar cells (DSSC) made of TiO2 have received increasing attention since O’Regan and Gratzel published their work in Nature in 1991 [1]. Some studies have been conducted to determine the effect of the TiO2 electrode thickness on the DSSC performance. Nevertheless, the effect of the electrode thickness on the J–V characteristics, especially the short circuit current density (Jsc), has not been adequately addressed. Therefore, in this investigation, parametric analyses were conducted to study the DSSC electrode thickness effect on Jsc. Diffusion model was used to derive the equation of nanoporous semiconductor film thickness (d) dependence on Jsc. TiO2 paste was prepared using same method as Ref. [2]. The cells I-V curve were characterized using a computerized digital multi-meter (Keithley 2400) with a variable load. The cells short circuit current (Jsc) data gotten from the I-V characterization were plotted as the function of the thickness of TiO2 films. The result of the data plot was then compared and fitted with the theoretical modelling result. It is apparent that the DSSC performance largely depends on the TiO2 film thickness. The results was also showed that the diffusion model provided good approximation to describe the dependence of Jsc on the film thickness of DSSC.DOI: http://dx.doi.org/10.17977/um024v4i12019p001